The shortest way home [large type] - Fay, Juliette (Thorndike Press, 2013)
Nurse Sean Doran returns from Africa and assumes the parental burden of caring for his aunt and nephew, a responsibility for which he is ill equipped. Soon, he reconnects with Becky, his childhood friend, but their budding romance is threatened by Sean's pathological reluctance to put down roots, and he has to finally decide what's most important to him.